Death certification status in Eastern Mediterranean Region: A systematic review. Issue 9 (21st October 2022) - Abed Alah, Muna; Alchawa, Mohamad; Ahmed, Salma; Osama, Mohammad; Kehyayan, Vahe; Bougmiza, Iheb
Abstract: A death certificate is an important public health surveillance tool that affects the quality of morbidity and mortality statistics. This systematic review examines death certification in the Eastern Mediterranean Region, uncovers the methodological qualities of published studies, the common errors committed by certifiers, and physicians' knowledge in filling out death certificates. We searched three databases, finding 19 studies, the majority of which reported errors in the underlying cause of death. Fewer than 25% of physicians reported training on filling out death certificates. Complexity of the cases and lack of training were reported as common difficulties facing physicians leading to errors.